ADAlı Magazine - Aliverdiyeva, Fakhriyya; Zeynalov, Rifah; Heybatova, Suel; Aliyeva, Turkana; Shirinova, Nigar; Aliyev, Kanan; Sadigzade, Emin; Qadirova, Ayan; Aliyev, Nihad; Ismayilova, Sariyya; Orujova, Nurjan; Zeinalova, Sabina; et al. (ADA University, 2023)
ADAlı Magazine is ADA University's new magazine club covering all areas of public life in the ADA community. ADAlı magazine, which started its work in 2022, mainly focuses on the new perspectives of ADA, with interviews, news, photos, and events. ADAlı magazine conducted more than 20 interviews, 8 events, 4 of which were donations, and hundreds of photos. Also, ADAli Magazine is one of the clubs that have successfully worked with many others promoting, supporting, and collaborating with them.
The University Magazine 2023
Keywords: ADA University--Newspaper.